Persepsi Masyarakat Terhadap Dampak Alih Fungsi Lahan Pertanian Menjadi Nonpertanian di Desa Bocek Kecamatan Karangploso Kabupaten Malang - Muttaqin, M. Rijalul; Wardani, Nila Restu; Jamil, Achmad Maulana Malik (PT. Pubsains Nur Cendekia, 2025)
The increasing need for space for urban activities has caused growth in urban areas to begin to move away from the city center and spread to outlying areas, one of which is the Bocek Village area, Karangploso District. The aim of this research is to determine the impact of land conversion from agricultural to non-agricultural. This study uses a qualitative descriptive research type. Data collection techniques in this study used interviews and documentation. The results of the study showed that the positive impacts of land conversion in Bocek Village include increasing economic growth, providing alternative sources of income, opening job vacancies, and becoming village tax revenue. The negative impacts include the creation of social gaps in terms of communication and socialization, decreased land fertility and agricultural harvest production, ecosystem damage and decreased soil quality.